Pasar Uang Antarbank Dengan Prinsip Syariah - Bhaswarendra Guntur Hendratri (JES (Jurnal Ekonomi Syariah), 2017)
Islamic banking development that is increasingly requires the development of Islamic banking products, which are used to meet the needs and demands of its customers. Islamic banking can overcome or manage their liquidity in an Islamic way, both the sukuk and other types of investments, which certainly does not violate the Islamic sharia. The keys are used by banks in their liquidity management is the availability of primary and secondary reserves. In fulfillment of secondary reserve, bank can invest idle fund in Money Market. Islamic interbank money market is able to support smooth for Islamic banking to use Islamic interbank money market as a means to organize and manage liquidity. Interbank money market with Sharia principle is one of the facilities provided by Bank Indonesia as control of Indonesia banking in terms of utilization of idle funds held by Islamic banking. Interbank money market with Sharia, which has the right to publish is only a BUS or UUS because, in the future, BUS or UUS will be the manager of the funds, both in terms of SIMA (Mudharabah Interbank Investment Certificate) or SIKA (Commodity Interbank Certificate). Commodity Certificates based on Sharia (SIKA) is different with SIMA. SIKA uses murabahah contract. The trade is conducted in the commodity exchange. The interbank money market with Sharia principles is not much different from the risks that exist in the money market in general. However, the risk in interbank money market seems more minimal because is conceptualized and organized by Bank Indonesia. Keywords: Sharia Money Market, Islamic Banking